Retinal structural and microvascular changes in myelin oligodendrocyte glycoprotein antibody disease and neuromyelitis optica spectrum disorder: An OCT/OCTA study - Lang, Yanlin; Kwapong, William Robert; Kong, Lingyao; Shi, Ziyan; Wang, Xiaofei; Du, Qin; Wu, Bo; Zhou, Hongyu (Frontiers in Immunology, 2023)
Purpose: To compare the optical coherence tomography (OCT)/OCT angiography (OCTA) measures in patients with neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein antibody disease (MOGAD) Methods: 21 MOG, 21 NMOSD, and 22 controls were enrolled in our study. The retinal structure (retinal nerve fiber layer, RNFL, and ganglion cell-inner plexiform layer, GCIPL) was imaged and assessed with the OCT; OCTA was used to image the macula microvasculature (superficial vascular plexus, SVP, intermediate capillary plexus, ICP, and deep capillary plexus, DCP). Clinical information such as disease duration, visual acuity, and frequency of optic neuritis and disability were recorded for all patients. Results: Compared with NMOSD patients, MOGAD patients showed significantly reduced SVP density (P = 0.023). No significant difference (P > 0.05) was seen in the microvasculature and structure when NMOSD-ON was compared with MOG-ON. In NMOSD patients, EDSS, disease duration, reduced visual acuity, and frequency of ON significantly correlated (P < 0.05) with SVP and ICP densities; in MOGAD, SVP correlated with EDSS, duration, reduced visual acuity, and frequency of ON (P < 0.05) while DCP density correlated with disease duration, visual acuity and frequency of ON. Conclusions: Distinct structural and microvascular changes were identified in MOGAD patients compared to NMOSD suggesting that the pathological mechanisms are different in NMOSD and MOGAD. Retinal imaging via the SS-OCT/OCTA might have the potential to be used as a clinical tool to evaluate the clinical features associated with NMOSD and MOGAD.